Efektifitas Penggunaan Kahoot! untuk Meningkatkan Hasil Belajar Siswa : Effectiveness of Using Kahoot! to Improve Student Learning Outcomes - Irwan, Irwan; Luthfi, Zaky Farid; Waldi, Atri (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to measure the effectiveness of the use of assessment learning media based on online games which is Kahoot to improve student learning outcomes. This study uses a quantitative approach with the quasi experiment method. The number of samples in each group is 30 people. The results shows that Kahoot can be an alternative interactive learning media in higher education because it is proven to significantly improve student learning outcomes with F (1.58) = 0.001, p <0.05 that means there are deferences between control and experiment class which is mean of experiment class (SD = 13.33, SD = 3.30) is higher than control class (M = 10.50, SD = 2.81)